Sustainability and Tourism Marketing: A Bibliometric Analysis of Publications between 1997 and 2020 Using VOSviewer Software - Cavalcante, William Quezado de F. (2021)
Several studies have empirically explored the association between practices in sustainable tourism and their impact on tourism marketing. However, bibliometric studies that organize the production in this field are still scarce. The objective of this study is thus to provide a bibliometric analysis of research on sustainable practices in tourism related to marketing, identifying the state of the art, trends and other indicators, by monitoring the articles published on the Web of Science (WoS) platform. A sample of 694 materials was obtained. The data were processed and the results graphically illustrated using the VOSviewer software. The study analyzed the simultaneous occurrence of publications by year, keyword trends, cocitations, bibliographic coupling and analysis of coauthorship, countries and institutions, and indicates that the literature on tourism sustainability issues in the field of tourism marketing is growing at a quick pace; merely five papers accounted for more than 2193 citations, but there are several prolific authors. Of the 694 sources included in the review, the most important ones published 40.34% of the papers; Spain is the leading country in this topic. This research provides insight about the state of the art and identifies gaps and research opportunities in sustainability and tourism marketing.